Registrum Palatinum Dunelmense: The Register of Richard de Kellawe, Lord Palatine and Bishop of Durham, 1311–1316. - Hardy, Thomas Duffus Sir (Cambridge library collection. Rolls, 1873)
This Latin Register of Richard Kellaw, Bishop of Durham (d.1316), is the earliest to survive for this important diocese, where the bishop held quasi-royal authority within his palatinate. He was an active bishop, and the Register, covering the years 1311–16, includes information about ordinations, indulgences, loans, grants and licences to study, as well as about Kellaw's secular administration of his diocese. During his five-year episcopate, he also had to deal with constant trouble from the Scots under Robert Bruce. This four-volume work, published as part of the Rolls Series between 1873 and 1878, was edited by the historian Sir Thomas Duffus Hardy (1804–78). It is an important source on the civil and ecclesiastical history of the North of England in the early fourteenth century. Volume 1 contains the first 140 folios (of 366), which comprise documents from the years 1311–14.